Inorganic Geochemical Study of the Siliciclastic Sediments penetrated by Ash-3 Well in the Greater Ughelli Depobelt, Niger Delta Basin, Nigeria - K. Itiowe; B. Kpege; O.N. Ekone; O.J. Aliu (Journal of Applied Sciences and Environmental Management)
Inorganic geochemical study of the siliciclastic sediments penetrated by Ash-3 Well was undertaken in order to classify the siliciclastic sediments, determine the provenance area, tectonic setting and the environment of deposition of the study area. Twenty eight (28) ditch cutting samples within the interval of 15ft to 11430ft were obtained for Xray fluorescence analysis to determine the major oxides composition. Using Herron’s plot for classification shows that the siliciclastic sediments were classified into Fe-shale, Fe-sand and quartz arenites fields. Roser and Korsch’s discriminant function diagrams for provenance signature and tectonic setting show quartzose sedimentary provenance and passive margin tectonic setting fields respectively. The environment of deposition from inorganic geochemical analysis shows that the sediments were deposited with in the continental and transitional environments.